LEADING, LAGGING, SYNCHRONIZED? BUSINESS CYCLES OF EU COUNTRIES BEYOND EUROZONE - Katarzyna Piłat (European Scientific Journal, ESJ, 2014)
The theory of optimum currency area is an important reference point in analyses of monetary integration processes. According to the optimum currency area theory one of the most important factors for countries planning to form a monetary union is business cycle synchronisation. The aim of the paper is to evaluate the level of business cycles’ synchronisation of European countries beyond euro zone with the fluctuation observed in the euro area. There are a few methods which are applied: periodograms, concordance index and cross-correlation coefficients. The results show that, on the basis of chosen measures, analysed countries exhibit relatively good level of business cycle synchronisation. Slightly worse result are obtained for Romania, both in case of cycle’s length and phase similarity.